The dual mediating effect of self-efficacy and motivation between conscientiousness and academic performance of university students in China: the moderated mediation effect of gender - Li, Jianan; Ma, Tingting; Lee, Chang Seek (Frontiers in Psychology, 2025)
In recent decades, there has been extensive research on the impact of personality on academic achievement, among which conscientiousness was verified to be a stable contributor. This study aims to clarify the moderated mediation relationship among conscientiousness, gender, academic self-efficacy, academic motivation, and academic performance. To achieve this purpose, the current study proposed a hypothesized model and verified it through a random sampling survey. With the informed consent of the respondents, the survey was conducted on 304 Chinese university students through the Wenjuanxing platform. For data research and analysis tools, SPSS and PROCESS macro were used, specifically, descriptive statistics analysis, reliability analysis, correlation analysis, and SPSS PROCESS macro model 83. The results indicated that conscientiousness, academic self-efficacy, academic motivation, and academic performance were positively correlated. Furthermore, gender moderated the mediating relationship from conscientiousness to academic self-efficacy, academic motivation, and academic performance. Such research results provided new ideas on how to improve the academic performance of college students, namely, focusing on and improving their academic self-efficacy and academic motivation. Meanwhile, it also provides more targeted help for the gender-differentiated characteristics of college students.